2012
DOI: 10.1159/000343168
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sugammadex in a Patient with Amyotrophic Lateral Sclerosis

Abstract: Objective: To report on general anesthesia management in amyotrophic lateral sclerosis. Case Presentation and Intervention: A 47-year-old man presented with fracture of the humerus. The patient was diagnosed with amyotrophic lateral sclerosis. General anesthesia was induced with propofol, rocuronium and remifentanil. After uneventful surgical repair, TOF (train-of-four) ratio reached >0.90 at the end of operation. However, muscle strength and tidal volume were inadequate. After sugammadex 2 mg kg-1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…In a patient with ALS reported by Kelsaka et al, clinical signs of inadequate recovery were observed despite a TOF ratio > 0.90. Two minutes after sugammadex 2 mg/kg was administered, the patient recovered clinically and was extubated uneventfully [58] (Table 5). A similar discrepancy between TOF ratio and clinical signs of muscle strength recovery was also reported by Chang et al [59,60].…”
Section: Neuropathies (Table 4)mentioning
confidence: 99%
“…In a patient with ALS reported by Kelsaka et al, clinical signs of inadequate recovery were observed despite a TOF ratio > 0.90. Two minutes after sugammadex 2 mg/kg was administered, the patient recovered clinically and was extubated uneventfully [58] (Table 5). A similar discrepancy between TOF ratio and clinical signs of muscle strength recovery was also reported by Chang et al [59,60].…”
Section: Neuropathies (Table 4)mentioning
confidence: 99%
“…The challenge is caused by the extreme sensitivity of this population to NMBAs, which could lead to an overlong period of mechanical ventilation that could trigger respiratory and cardiovascular complications and also result in death [44]. Therefore, the combination rocuronium-sugammadex seems to be a safe and reliable option for patients with myasthenia gravis, multiple sclerosis, dermatomyositis, Sjogren's syndrome, Becker muscular dystrophy, Duchene muscular dystrophy, myotonic dystrophy, spinal muscular atrophy, StrumpellLorrain disease, and amyotrophic lateral sclerosis [10,42,[45][46][47][48][49][50]. The rocuronium-sugammadex combination has been studied mainly in patients with myasthenia gravis.…”
Section: Advantages Of Sugammadex In Patients With Comorbidities Patimentioning
confidence: 99%
“…65 However, there are case reports of patients with ALS who underwent neuromuscular blockade and recovered quickly with the use of suggamadex. 66,67 Increased risk of malignant hyperthermia or rhabdomyolysis has not been reported in patients with ALS. 64 …”
Section: Surgical Risksmentioning
confidence: 99%